-25=p-3

Simple and best practice solution for -25=p-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25=p-3 equation:


Simplifying
-25 = p + -3

Reorder the terms:
-25 = -3 + p

Solving
-25 = -3 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-25 + -1p = -3 + p + -1p

Combine like terms: p + -1p = 0
-25 + -1p = -3 + 0
-25 + -1p = -3

Add '25' to each side of the equation.
-25 + 25 + -1p = -3 + 25

Combine like terms: -25 + 25 = 0
0 + -1p = -3 + 25
-1p = -3 + 25

Combine like terms: -3 + 25 = 22
-1p = 22

Divide each side by '-1'.
p = -22

Simplifying
p = -22

See similar equations:

| 1+8x=85 | | x+2=-28 | | 3(4x+12)=2x-24 | | ac=bd | | c=b-d | | 12x-8=2x+6 | | 9r^2-17r+8=0 | | 7x+5x+10=x | | 2.5h-15=4 | | x^4-6x^3+9x^2+4x-12=0 | | x^4-6x^3+9x^2+4x=12 | | A+1.25=2a | | 35=3x+4 | | 12x^2+43x+35=0 | | 6r^2+7r-3=0 | | 8(x-3)=18+x | | 11a+10=0 | | x^2-.06x+.24=0 | | x-(20)*0.5=(x)*0.5+20 | | -1=1.6b+3.8 | | 2x^2-.12x+.48=0 | | 9x-36x+5x-20= | | .50x+6-3x+.50=3.5 | | .66-6h=2.16 | | x(28+4x)=72 | | 9h+22=-5h-17 | | 12a-64=-64 | | 5(c+5)=3(c+11) | | 9(m+3)=3m-21 | | -5.55=0.3x-2.5-2.6 | | .25x+125-.10=20.45 | | 11x^2-66x=0 |

Equations solver categories